Steel design - McMullin, Paul W. ;McMullin, Paul W. ;Seelos, Richard T. (New York : Routledge, 2018)
Steel Design covers steel design fundamentals for architects and engineers, such as tension elements, flexural elements, shear and torsion, compression elements, connections, and lateral design. As part of the Architect$1 (Bs Guidebooks to Structures series it provides a comprehensive overview using both imperial and metric units of measurement. Each chapter includes design steps, rules of thumb, and design examples. This book is meant for both professionals and for students taking structures courses or comprehensive studies. As a compact summary of key ideas, it is ideal for anyone needing a quick guide to steel design. More than 150 black and white images are included.s
1.LeBow Business Building -- 1.1.Introduction -- 1.2.Design Development -- 1.3.Construction Documents -- 1.4.Construction Administration -- 1.5.Opening -- 2.Steel Fundamentals -- 2.1.Historical Overview -- 2.2.Codes -- 2.3.Materials -- 2.4.Material Behavior -- 2.5.Structural Configuration -- 2.6.Section Types and their Properties -- 2.7.Construction -- 2.8.Quality Control -- 2.9.Where We Go from Here -- 3.Steel Tension -- 3.1.Stability -- 3.2.Capacity -- 3.3.Demand vs Capacity -- 3.4.Deflection -- 3.5.Detailing -- 3.6.Design Steps -- 3.7.Example: Tension Member Design -- 3.8.Where We Go from Here -- 4.Steel Bending -- 4.1.Stability -- 4.2.Capacity -- 4.3.Demand versus Capacity -- 4.4.Serviceability Limit States -- 4.5.Design Steps -- 4.6.Example: Flexural Member Design -- 4.7.Where We Go from Here -- 5.Steel Shear and Torsion -- 5.1.Stability -- 5.2.Capacity -- 5.3.Demand vs Capacity -- 5.4.Deflection -- 5.5.Detailing -- 5.6.Design Steps Note continued -- 5.7.Design Example -- 5.8.Where We Go from Here -- 6.Steel Compression -- 6.1.Stability -- 6.2.Capacity -- 6.3.Demand vs Capacity -- 6.4.Deflection -- 6.5.Design Steps -- 6.6.Design Example -- 6.7.Where We Go from Here -- 7.Steel Lateral Design -- 7.1.Introduction -- 7.2.Lateral Load Paths -- 7.3.Diaphragms -- 7.4.Lateral System Types -- 7.5.Seismic Design Considerations -- 7.6.Where We Go from Here -- 8.Steel Connections -- 8.1.Connector Types -- 8.2.Capacity -- 8.3.Demand vs. Capacity -- 8.4.Detailing -- 8.5.Design Steps -- 8.6.Design Example -- 8.7.Where We Go from Here.
Includes bibliographical references and index.
Keywords: STRUCTURAL DESIGN